Study on determination of an object material using the microwave doppler sensor. Issue 1 (April 2021) - Oda, K; Nakamura, K; Ikebata, K; Kobayashi, Y
Abstract: In this study, to consider a method for detecting the sediment portion of avalanches containing sediment using microwave Doppler sensors, we confirmed whether the signal processing obtained by the sensors can differentiate the objects. Since microwaves in this frequency band are not easily affected by rain and snowfall, these are being developed for use in dashboard camera and other applications. However, it is necessary to understand the attenuation of the microwave for the snow in order to apply this technology to detect the sediment in the avalanche. It is also necessary to know the rate of reflection of microwaves from the snow and sand. Therefore, it is necessary to verify whether the reflection of the microwave from the sediment is correctly measured or not. In this report, we discuss the results of the verification to see if the distance between the sensor and the object, which is known in advance, can be detected correctly.